Ambivalence in The Regulation of Indigenous Peoples' Rights in Indonesia's Legal Hierarchy - Andika Prawira Buana; Arsy , Muhammad (Department of Law, Universitas Islam Negeri Alauddin Makassar, 2024)
The recognition and protection of indigenous peoples in Indonesia remain uncertain due to the absence of ratified laws specifically addressing their rights. This lack of legal instruments undermines their recognition and protection, leading to uncertainty regarding their traditional rights. This article aims to identify potential arrangements for derivative regulations to address this gap. Normative legal research, employing a legislative and conceptual approach, was utilized. The findings suggest that while legal recognition of indigenous peoples exists in various laws, regional regulations tailored to local conditions are necessary. However, there's no consensus on which regulations should serve as the basis for these regional laws. Recommendations propose that the Agrarian Law, Human Rights Law, Village Law, and Job Creation Law could inform regional regulations to recognize, protect, and fulfill the traditional rights of indigenous peoples, thereby mitigating dualism of authority.